Temporal and spatial variations of 134Cs and 137Cs levels in the Sea of Japan and Pacific coastal region: Implications for dispersion of FDNPP-derived radiocesium. (February 2018) - Inoue, M.; Shirotani, Y.; Yamashita, S.; Takata, H.; Kofuji, H.; Ambe, D.; Honda, N.; Yagi, Y.; Nagao, S.
Abstract: To investigate the dispersion of Fukushima Dai-ichi Nuclear Power Plant (FDNPP)-derived radiocesium in the Sea of Japan and western Pacific coastal region and determine the sources of radiocesium in these areas, we examined the temporal and spatial variations of 134 Cs and 137 Cs concentrations (activities) during 2011–2016 in seawaters around the western Japanese Archipelago, particularly in the Sea of Japan. In May 2013, the surface concentration of 134 Cs was ∼0.5 mBq/L (decay-corrected to March 11, 2011), and that of 137 Cs exceeded the pre-accident level in this study area, where the effects of radiocesium depositions just after the FDNPP accident disappeared in surface waters in October 2011. Subsequently, radiocesium concentrations gradually increased during 2013–2016 (∼0.5–1 mBq/L for 134 Cs), exhibiting approximately homogeneous distributions in each year. The temporal and spatial variations of 134 Cs and 137 Cs concentrations indicated that FDNPP-derived radiocesium around the western Japanese Archipelago, including the Sea of Japan, has been supported by the Kuroshio Current and its branch, Tsushima Warm Current, during 2013–2016. However, in the Sea of Japan, the penetration of 134 Cs was limited to depths of less than ∼200 m during three years following the re-delivery of FDNPP-derived radiocesium. Graphical abstract: Highlights: We examined radiocesium concentrations at surface in the Sea of Japan (2011–2016). Radiocesium concentrations were higher relative to the pre-accident level in 2013. Radiocesium gradually increased during 2013–2016 with homogeneous distribution. 228 Ra concentrations were employed to study the migration pattern of radiocesium. Radiocesium has been continually delivered with the Kuroshio Current water.